Augmented Reality in Natural Sciences and Biology Teaching: Systematic Literature Review and Meta-Analysis - António Faria; Guilhermina Lobato Miranda (Ital Publication, 2024)
This article presents the results of a systematic literature review followed by a meta-analysis of studies on the use of Augmented Reality (AR) in the teaching and learning of Natural Sciences and Biology, among primary and secondary school students. The variables considered were the effects on student learning and motivation, as well as other variables like students understanding and students’ perception of the cognitive load. The teaching contexts and strategies used in association with AR were also considered. The PRISMA methodology was used in articles published between 2010 and 2023, in EBSCO, Science Direct, Scopus, Springer Link, Taylor & Francis and Web of Science databases. Seven hundred and twenty-one articles (721) were found, which, after applying the inclusion and exclusion criteria, were reduced to 15. The results showed that, in most studies, AR associated with certain teaching strategies and using a quasi-experimental research methodology produced better results in learning and student motivation and other variables such as student understanding and memorization (from Bloom's taxonomy), and perception of cognitive load. The overall analysis of the data allowed us to observe a strong effect size value (d = 1.13 [0.39;1.86]) in favour of the experimental group regarding learning and a moderate effect on motivation when using AR (d = 0.52 [0.30;0.74]). The same occurred with other variables studied where students obtained better results, which translated into a small or medium effect size. For example, in the perception of cognitive load, the effect size was d= 0.73. Doi: 10.28991/ESJ-2024-08-04-025 Full Text: PDF